Analysis of Bisphenol A in Blood and Urine Samples: A Mini Review - Taskeen, Abida; Naeem, Ismat (Asian Journal of Chemistry, 2010)
Bisphenol A is constantly discharged at trace levels in food packed in metal cans with PVC linings. This is also present in bottled water. This represents a cause for concern because of potential effects of bisphenol A to human health. We compiled data on the methods used for analysis of bisphenol A in blood and urine samples published in the last 10 years.